2022
DOI: 10.3389/fsurg.2022.819018
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance and Gene Expression Characteristics of Gastric Signet-Ring Cell Carcinoma: A Study Based on the SEER and TCGA Databases

Abstract: PurposeThis study is based on the Surveillance, Epidemiology, and End Results (SEER) program to explore the prognostic differences between signet-ring cell carcinoma (SRC) and intestinal-type gastric carcinoma (ITGC). This study is also based on gene sequencing data from The Cancer Genome Atlas (TCGA) to identify unique genetic contributions to the prognostic differences between the two subtypes of gastric cancer.Patients and MethodsThe clinical data were based on the SEER database from 2004 to 2015. Kaplan–Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Ma et al [34] correlated with the present results as they revealed that SERPINE1 was associated with poor prognosis of GC by being involved in multiple immune cell infiltrates in gastric cancer. Also, Akhavan et al [35] agreed with the present findings as they identified SERPINE1 as one of the four genes upregulated in GC suggesting that these genes being predicted targets of hsa-miR-421 and hsa-miR-193a-3p.…”
Section: Discussionsupporting
confidence: 88%
“…Ma et al [34] correlated with the present results as they revealed that SERPINE1 was associated with poor prognosis of GC by being involved in multiple immune cell infiltrates in gastric cancer. Also, Akhavan et al [35] agreed with the present findings as they identified SERPINE1 as one of the four genes upregulated in GC suggesting that these genes being predicted targets of hsa-miR-421 and hsa-miR-193a-3p.…”
Section: Discussionsupporting
confidence: 88%
“…The molecular interactions in the process of gene expression include transcription factor-transcription initiation factor, transcription factor-cofactor, cofactor-cofactor, translation initiation factor-cofactor, modi cation factor and so on. The interaction between serpine 1 and THBS1 has been veri ed in the process of gastric cancer and luteinization in endothelial cells [50,51]…”
Section: Discussionmentioning
confidence: 99%
“…This stage of carcinoma is the classical early gastric SRCC. It includes classical-type signet-ring cell (the cell is round, with a diameter of 15-30 mm and reddish mucous substances in the cytoplasm; the nucleus is deviated, and is signet-ring or crescentshaped), and those that we previously reported: juvenile signet-ring cell (the cell is round or irregular, and the cytoplasm is strongly eosinophilic; the nucleus is irregularly round or oval, and deviated, and the ratio of nucleus to cytoplasm is 1:1-3; the nuclear chromatin is basophilic and eosinophilic); hyperproliferative type signet-ring cell (the cell is round or oval, the cytoplasm is uniform and slightly stained with basophilic and eosinophilic mucus; the nucleus is large with a prominent nucleolus, and is deviated); nuclear-free vacuolated signet-ring cell (the cell developed due to the relationship between sections during section preparation; the cell still maintained the cytoplastic outline and had reddish mucous substances in the cytoplasm); degenerative signet-ring cell (the size of the cell increased, and was mostly 20 mm-40 mm, or up to 50 mm; the membranes were incomplete, the nucleus was small and slightly stained, and gray, or it had no nucleus) (23). In this study, when small signet-ring cell carcinoma-like lesions or foveolar-type signet-ring cell carcinoma infiltrated into the lamina propria of the mucosa and the submucosa, signet-ring-like heterocysts and small signet-ring cell carcinoma-like lesions, after reproliferation, differentiated into various types of gastric adenocarcinoma with signet-ring cell…”
Section: Discussionmentioning
confidence: 99%
“…Multistage carcinogenesis of SRCC involving genetic and epigenetic aberrations is associated with stage-dependent prognosis (22). There are significant differences in clinicopathological features and prognosis between signet ring cell carcinoma (SRC) and intestinal type gastric cancer (ITGC) (23). In gastric cancer with signet ring cell (SRC) component, there is a good prognosis in stage I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation